Pelatihan Menganalisis dan Menyelesaikan Soal Matematika Berorientasi Higher Order Thingking Skills (HOTS) bagi Guru SMA Kabupaten Padang Pariaman - Khairudin Khairudin; Niniwati Niniwati (Jurnal Pengabdian Pada Masyarakat, 2020)
TRAINING ON TIPS FOR ANALYZING AND SOLVING HIGHER ORDER THINGKING SKILLS (HOTS) ORIENTED MATHEMATICS PROBLEMS FOR HIGH SCHOOL TEACHERS IN PADANG PARIAMAN REGENCY. Curriculum 13 has not been fully implemented by teachers in secondary schools, especially senior high schools in the Pariaman area. In general, not many teachers understand the concept of assessment based on High Order Thingking Skills (HOTS). The limited of government program to provide training is one of the factors that makes teachers unfamiliar with HOTS-oriented questions. Its impact on students is seen in learning outcomes that are less encouraging at the national or international level. PPM activities carried out on July 25, 2019 in SMN 1 Sicincin Padang Pariaman. From the evaluation of the activity, it was obtained that the training was at a good level and continued with training per Math sub-material, by collaborating through institutions. At the time of the training, due to time constraints and the need of Mathematics teachers, only discussed Calculus and Geometry (Three Dimension).